2017
DOI: 10.1177/1545968317744277
|View full text |Cite
|
Sign up to set email alerts
|

Prism Adaptation in Rehabilitation? No Additional Effects of Prism Adaptation on Neglect Recovery in the Subacute Phase Poststroke: A Randomized Controlled Trial

Abstract: No beneficial effects of PA over SA in the subacute phase poststroke were observed, which was comparable for situations of varying complexity. Heterogeneity of the syndrome, time post-stroke onset, and the content of treatment as usual are discussed. Basic knowledge on subtypes and recovery patterns would aid the development of tailored treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 52 publications
0
52
2
9
Order By: Relevance
“…[94][95][96][97] A possible explanation of negative findings might be that visuomotor adaptation (ie, aftereffect) has to reach a critical threshold to affect performance in other tasks. 98 Given the high intra-and interindividual variability of individuals with USN, visuomotor adaptation induced by low power prisms (i.e., shifting the visual field of 5°, 6°or 10°)as those used in RCT studies that did not find any beneficial outcomes after PA [94][95][96][97] might be too small to produce detectable effects in all patients. The fact that the critical threshold can only be reached with prisms of high power (i.e., shifting the visual field of 10°or 12°, as those used in the above studies that found significant PA effects) might explain some negative findings.…”
Section: Prismatic Adaptationmentioning
confidence: 99%
“…[94][95][96][97] A possible explanation of negative findings might be that visuomotor adaptation (ie, aftereffect) has to reach a critical threshold to affect performance in other tasks. 98 Given the high intra-and interindividual variability of individuals with USN, visuomotor adaptation induced by low power prisms (i.e., shifting the visual field of 5°, 6°or 10°)as those used in RCT studies that did not find any beneficial outcomes after PA [94][95][96][97] might be too small to produce detectable effects in all patients. The fact that the critical threshold can only be reached with prisms of high power (i.e., shifting the visual field of 10°or 12°, as those used in the above studies that found significant PA effects) might explain some negative findings.…”
Section: Prismatic Adaptationmentioning
confidence: 99%
“…By contrast, one study described mixed results, as patients treated with PA showed greater improvement than Controls after treatment, but group results were indistinguishable after one month (Nys, de Haan, Kunneman, de Kort, & Dijkerman, 2008). More disappointingly, no effects additional to spontaneous recovery were measured by four studies that included a total number of 72 patients treated with prisms (Mancuso et al, 2012;Rode et al, 2015;Ten Brink et al, 2017;Turton, O'Leary, Gabb, Woodward, & Gilchrist, 2010). In addition, some positive findings are not really compelling and raise thè question of their clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Improved visuospatial unilateral neglect symptoms as a result of rehabilitation may translate to improvements in the art constructive errors of painting. Some other clinical trials did not find such an effect for the prism (Barrett, Goedert, & Basso, 2012;Ten Brink et al, 2017;Turton, O'Leary, Gabb, Woodward, & Gilchrist, 2010).…”
Section: Discussionmentioning
confidence: 88%